Engaging Without Exposing: Use of a Fictional Character to Facilitate Mental Health Talk in Focus Groups With Men Who Have Been Subject to the Criminal Justice System. (November 2018) - Owens, Christabel; Carter, Mary; Shenton, Deborah; Byng, Richard; Quinn, Cath
In an effort to encourage men with experience of being subject to the criminal justice system to contribute to focus group discussions on the sensitive topic of mental health, while also doing our utmost to protect them from discomfort or risk of exploitation, we used a novel technique involving the creation of a fictional character, supplemented by an audio-recorded vignette. We studied the role played by this technique in achieving our stated aims of "engaging without exposing." In this article, we report on the use of this technique in three focus groups, showing how in very different ways it shaped the interaction between participants and generated crucial insights into the lives and service needs of each group. We conclude that the technique may lend itself to being used in focus groups with other marginalized or seldom-heard populations.